IgG4 Related Peri-aortitis: A Case Diagnosed in Combined Military Hospital, Dhaka (Journal of Armed Forces Medical College, Bangladesh, 2020)
IgG4 related disease is a multi-organ immune-mediated condition which links many disorders previously regarded as isolated, a single-organ disease without any known underlying systemic condition. It may mimic anymalignant, infectious and inflammatory disorders. It was recognized as a unified entity only 10 years ago. Histopathology is the key to diagnosis. The three central pathology features of IgG4 related disease are lymphoplasmacytic infiltration, stroriform fibrosis, and obliterative arteritis. It is important to promptly diagnose IgG4 related disease because this disease commonly manifests as swelling of the affected organs, which must be differentiated from true neoplasms. Periaortitis or periarteritis is one of the clinical features of IgG4 related diseases. IgG4 related arterial lesions occur mainly in the aorta and its main branches and radiologically characterized by homogeneous arterial wall thickening corresponding to pathological features of IgG4 related sclerosing inflammation in the adventitia. There are 5 types of IgG4 related peri-aortitis, out of which Type 2 is most common. IgG4 related peri-aortitis generally respond to glucocorticoids in its inflammatory stage, but recurrent or refractory cases are common. Greater awareness of this disease is needed to ensure earlier diagnoses to prevent severe organ damage. A 38-year-old male was diagnosed as Type 2 IgG4 related periaortitis 2 years ago in CMH, Dhaka. He was treated with oral steroid and Azathioprine with a rewarding outcome.Journal of Armed Forces Medical College Bangladesh Vol.14 (2) 2018: 217-219